Organizational and Functional Procedures of Innovative Product Design in the Greek Business Context - Sdrolias, Labros; Bitzenis, Aristidis; Kakkos, Nikolaos; Kontakos, Panagiotis; Aspridis, Georgios; Škodová Parmová, Dagmar; Dvořáková Líšková, Zuzana; Belias, Dimitrios; Blanas, Nikolaos; Dachmiri, Kleoniki (University of Macedonia, 2018)
The phenomenon of domination of several powerful trading countries in the international market, which import semi-finished food products from the economically and commercially weaker countries, slightly process or standardize them and channel them for their final consumption arrogating their qualitative superiority, is an undeniable fact with major negative economic, and not alone, consequences for the countries of origin. In this category of the weakest countries naturally belongs Greece. Based on these brief remarks, the purpose of this work is the search for and formulation of effective ideas, organizational processes and functional procedures in the form of a "model" for the production of innovative products, capable not only to rapidly penetrate the international market, but also to steadily control a substantial part of it. Besides, the policy of innovative production management is scientifically recognized as a modern form of "national defense" in the face of contemporary globalization and Greece mustn’t ignore it.
Keywords: Innovation Products; Innovation Model; Innovation Process; International Markets; Organizational and Functional Procedures; Entreprises; Greece